'Through the lens of ethnography': Perceptions, challenges, and experiences of an early career practitioner-researcher in professional football. Issue 4 (7th August 2020) - Champ, Francesca; Ronkainen, Noora; Nesti, Mark S; Tod, David; Littlewood, Martin
ABSTRACT: The present study critically explores the use of practitioner-researcher ethnography in professional football, and illustrates some of the challenges that the first author experienced as a result of the dual-role occupation. The first author occupied the position of insider sport psychology practitioner-researcher within one professional football club over a 3-year duration. Traditional ethnographic research methods were employed, including; observations, field notes, and reflections. Following thematic analysis, research on the potential for conflict and tension in ethnography, and ethical guidelines from caring professions (e.g. sport psychology, health, and nursing) were used to make sense of the data. A series of reflective extracts highlight moral, ethical, and personal challenges of occupying a dual role, including threats to identity, acceptance of academics in elite sport, and confidentiality. For those individuals whose livelihood is dependent on their successes as a practitioner-researcher an understanding of how to overcome methodological challenges will be beneficial in improving their organisational status. From the results of this study, we suggest that a range of support mechanisms (e.g. ethnographers club, regional support hubs, supervisor/researcher training and education), and the development of a clear sense of self are essential for the ethnographic practitioner-researcher.